(untitled) (Texas Journal of Multidisciplinary Studies, 2022)
The article is devoted to the development of shopping centers, as well as open spaces. The content and essence of shopping centers and open spaces are discussed, its specific aspects and existing problems are revealed, the impact of shopping centers and open spaces on the external environment is given, and recommendations are given for improving the internal environment.